Layer selective magnetometry in ultrathin magnetic structures by polarised neutron reflection - Bland, J; Lee, J; Hope, S; Lauhoff, G; Penfold, J; Bucknall, D (1997)
We discuss the application of polarised neutron reflection to layer selective vector magnetometry measurements in thin magnetic films. To illustrate the application of PNR, we review recent measurements of the absolute moment in X/Fe/Ag(001) structures with X = Pd, Ag, Au and Cu and compare the results with the predictions based on theoretical calculations which take into account the measured interface roughness. For the case of strained fct Ni/Cu(001) structures we illustrate the use of PNR as a self-calibrating magnetometric technique in determining both the magnetic layer thickness and total sample moment for which a reduced moment per Ni atom is observed. Finally we present measurements of the layer dependent moments in FeNi/Cu/Co spin valve structures. We show that by comparing the PNR measurements with SQUID magnetometry measurements of the total sample moment we are able to determine the interface moments on an atomic scale. Copyright © 1997 Elsevier Science B.V. All rights reserved.